Enhancing Access to Justice: Comparative Insights into Mobile Courts in Indonesia and Malaysia - Hazar Kusmayanti; Nurul Hidayat Ab Rahman (Universitas Negeri Semarang, 2025)
This research aims to compare the mobile court case settlement practices in Malaysia and Indonesia, such as legal framework and jurisdiction, operational structure, successes and challenges and implementation strategies in both countries. Research methods used in this paper is a normative juridical approach, and the collection of data is conducted through statutory law: gathering relevant statutes, regulations, and legal provisions governing the establishment and operation of mobile courts in Indonesia and Malaysia. The findings reveal a comparison of mobile court case settlement practices in Malaysia and Indonesia, where the mobile court service is advantageous because it facilitates access to the court for justice seekers. Beyond the logistical benefits, these services offer psychological comfort by allowing proceedings to occur in familiar and less intimidating environments. The difference in the implementation of mobile courts is that in Indonesia mobile courts only exist at the district level religious courts, where judges go to the field to conduct trials in rural locations, for example in the village hall, and the cases handled only involve minor cases such as isbat marriage, divorce, divorce, child custody and determination of heirs. To overcome the geographical and logistical challenges, enhancing collaboration between different government agencies is crucial. In both countries, coordination between the judiciary, local governments, and other relevant agencies, such as transportation and communication departments, can improve the effectiveness of mobile courts.